Regulatory and policy analysis of employment and health protections in Indonesia’s creative economy - Afrilies Marlia Hafny; Naili Yuris Tri; Lina Angie Angel (BIO Web of Conferences)
This research explores the growing role of the creative economy and the regulatory gaps that impact labor protection, specifically in the creative industry sector. The digital transformation of the creative sector has led to significant economic contributions but also challenges regarding labor protection, especially health security for workers. Despite advancements, such as the introduction of social health insurance in Vietnam, Indonesia faces regulatory shortcomings in providing adequate health protection for creative workers, many of whom are freelancers or contract workers. Using a normative legal research method, this study analyzes key legal frameworks, including laws related to manpower, social security, and creative economy regulations, to assess the extent to which existing policies address labor and health protection in the digital era. The research highlights critical gaps in health coverage for workers with less than six months of employment and suggests that expanding social security coverage, increasing legal literacy, and enacting targeted regulatory reforms are essential for creating a more inclusive and sustainable creative economy workforce. The study also draws lessons from Vietnam’s successful implementation of Social Health Insurance. By addressing these regulatory shortcomings, Indonesia can better ensure the welfare of creative workers and enhance their contributions to the national economy.